Current-current deformations, conformal integrals and correlation functions - Giribet, Gaston Enrique (2020)
Motivated by the recent work on TT¯ -type deformations of 2D CFTs, a especial class of single-trace deformations of AdS3/CFT2 correspondence has been investigated. From the worldsheet perspective, this corresponds to a marginal deformation of the σ - model on AdS3 that yields a string background that interpolates between AdS3 and a flat linear dilaton solution. Here, with the intention of studying this worldsheet CFT further, we consider it in the presence of a boundary. In a previous paper, we computed different correlation functions of this theory on the disk, including the bulk 1-point function, the boundary-boundary 2-point function, and the bulk-boundary 2-point function. This led us to compute the anomalous dimension of both bulk and boundary vertex operators, which first required a proper regularization of the ultraviolet divergences of the conformal integrals. Here, we extend the analysis by computing the bulk-bulk 2-point function on the disk and other observables on the sphere. We prove that the renormalization of the vertex operators proposed in our previous works is consistent with the form of the sphere N -point functions.